Accelerated Amortization and Industrial Concentration - Selden, Richard T. (The Review of Economics and Statistics, 1955)
A S the pages of this journal testify,' economists recently have displayed a lively interest in the trend of industrial concentration. Those fearful of increased concentration in years to come are likely to be particularly concerned over the implications of continued heavy defense outlays. Although the evidence is far from convincing, many believe that the World War II mobilization program intensified industrial concentration. The issue examined in this article is whether a particular mobilization measure, accelerated tax amortization, has contributed toward increased concentration in American manufacturing industries during the current defense build-up.